A Randomized Controlled Trial to Assess the Effectiveness of Oral Rehydration Solution on the Natremic Status of Operated Patients with Traumatic Brain Injury - Kumari, Renu; Dhandapani, Manju; Kaur, Sukhpal; Singla, Navneet; Medhi, Bikash (Indian Journal of Neurosurgery, 2015)
Background Sodium alterations are very common among patients with the postoperative traumatic brain injury (TBI). It can be hyponatremia or hypernatremia. Sodium disturbances can lead to serious complications and adverse outcomes including death.Aim The current study was performed to assess the effectiveness of oral rehydration solution (ORS) on natremic status of patients with postoperative TBI.Materials and Methods The study was performed in the Department of Neurosurgery of a tertiary care hospital. Total 100 patients on Ryles tube were randomly allocated. The tools used were semistructured interview schedule and biophysiologic methods. In the intervention group, administration of ORS was started on second postoperative day till fifth postoperative day. Serum sodium levels were assessed daily from zeroth postoperative day to fifth postoperative day in both groups.Statistical Analysis and Result Both the groups were homogeneous and comparable. The mean serum sodium levels before and after the intervention were not significantly different in both groups. The proportion of patients with normonatremia was significantly greater in the intervention group on third through fifth postoperative days, that is, 76, 78, and 82%, as compared with that in the control group, that is, 52, 52, and 60%. The proportion of the patients with hyponatremia was high on third through fifth postoperative days in the control group as compared with that in the intervention group. The hypernatremia developed varied from 8 to 18% in both the groups.Conclusion Thus to prevent sodium imbalance, ORS can be safely administered to the patients with postoperative TBI without increasing the risk of hypernatremia.
Keywords: traumatic brain injury; oral rehydration solution; hyponatremia; normonatremia; hypernatremia